مفقود الخبر کے احکام پر سماجی تغیرات کے اثرات؛ایک تجزیاتی مطالعہ: Effects of social changes on rules of Mafqood-ul-Khabar; An analytical Review - Khan, Shahbaz (Al-Amīr Research Journal for Islamic Studies, 2024)
Mafqūd ul-Khabar (مفقود الخبر) means a person who is missing from his family and no one knows anything about him whether he is alive or dead. According to the Hanafi school of Law, a woman should wait for her disappearing husband at least 60 years leading to rest of her life. In this regard, imam Malik’s religion is more appropriate and convenient. Even Hanafi jurists also adopted this because it is so difficult for a wife to wait almost 60 years or the rest of her life for her husband. For example, according to the current law in Pakistan, if the husband has been disappeared for 4 years, in such a case, wife has been given the right of Tansīkh ((تنسیخ by the court, but in such a case the court-order has been kept in a stand for six months. Our current law gives a relaxation of four years to have been taken from the jurisprudence of Maliki. In view of the prevailing laws, they also have a period of time in case of husband's involvement, but the period of disappearance of the husband in Iraq is 4 years, whereas in Egypt, Morocco and Jordan this period is one year, so according to the law of these countries, the wife will wait for one year. Key Words: Mafqūd al-Khabar, Missing Husband, School of law, Tansīkh, Courts.